2015
DOI: 10.1002/cne.23863
|View full text |Cite
|
Sign up to set email alerts
|

Age effects on the nucleus of the lateral olfactory tract of the rat

Abstract: The olfactory deficits that occur during aging influence the quality of life and have been regarded as a risk factor for malnutrition in the elderly. The nucleus of the lateral olfactory tract (nLOT) is a cortical nucleus of the pallial amygdala that has been implicated in feeding behavior. Here we present quantitative data on the anatomy of the nLOT in the adult rat and on the effects of age on its structure and neurochemistry. Total neuron numbers, neuronal volumes, and volumes of layers 1-3 of the nLOT were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 83 publications
0
10
0
Order By: Relevance
“…The nucleus of the lateral olfactory tract (nLOT) is a small three-layered structure, with a volume of 0.24 mm 3 and 19,000 neurons (Vaz et al 2016 ). It is located in the ventral surface of the brain interposed between the anterior amygdaloid area and the anterior medial amygdala (Ennis et al 2015 ), and is related laterally with the anterior cortical amygdaloid nucleus (de Olmos et al 2004 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The nucleus of the lateral olfactory tract (nLOT) is a small three-layered structure, with a volume of 0.24 mm 3 and 19,000 neurons (Vaz et al 2016 ). It is located in the ventral surface of the brain interposed between the anterior amygdaloid area and the anterior medial amygdala (Ennis et al 2015 ), and is related laterally with the anterior cortical amygdaloid nucleus (de Olmos et al 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…Along with its peculiar neurogenic pattern, the nLOT also stands up as a unique region within the group of the cortical pallial nuclei due to some particular aspects of its morphology, neurochemistry and connections. It displays a distinctive three-layered organization (Price 1973 ; McDonald 1983 ; Millhouse and Uemura-Sumi 1985 ; Vaz et al 2016 ) and its layer 2 neurons, which are relatively large and represent over 80% of the total neuronal population of the nLOT (Vaz et al 2016 ), express a type of vesicular glutamate transporter (type 2) that is considerably less abundant, or even non-existent, in other areas of the pallial amygdala (Hur and Zaborszky 2005 ). It has a much higher density of heavy metals (Friedman and Price 1984 ) and stains more intensely for cholinergic markers (Millhouse and Uemura-Sumi 1985 ; Vaz et al 2016 ) than the surrounding structures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also demonstrated that the go-cue and no-go-cue responsive neurons highly contributed to the population dynamics of cue encoding and decoding, for accuracy of the animal's choices (Figure 5), suggesting that these bidirectional response neurons for cue odors effectively provided sufficient information to account for the behavioral choices. These bidirectional cues encoding a small number of neurons with a high level of information may be effective in the NLOT with only a small volume of 0.24 mm 3 and 19,000 neurons (Vaz et al, 2016).…”
Section: Electrophysiological Features Of Nlot Neuronsmentioning
confidence: 99%
“…Olfactory information is transmitted into the nLOT with a three-layered structure (layers I, II, and III). The nLOT layer Ⅱ neurons contributing to over 80% of the total neuronal population of the nLOT (17), project to the dwarf cell regions in the OT (6). The OT sends a major projection to the ventral pallidum regulating expected positive and negative valences (21)(22)(23).…”
Section: Neural Circuits Including the Nlotmentioning
confidence: 99%